Impact of Gender on the Various Aspects of Digital Payment System: A Banking Empirical Study from India - Menezes , Amith Donald; Kavyashree, K (Electronic Journal of Business and Management, 2023)
As digital payment systems continue to gain prominence in the modern economy, understanding the role of gender in shaping individuals' interactions with these systems becomes increasingly vital. This empirical study investigates the impact of gender on various aspects of digital payment systems, including adoption rates, usage patterns, perceptions, and barriers to adoption. Through a comprehensive analysis of survey data collected from a diverse sample of users, this research explores how gender influences individuals' preferences, behaviours, and attitudes towards digital payments. The findings shed light on gender disparities in access to and utilization of digital payment technologies, highlighting the need for gender-sensitive approaches to design, marketing, and policy-making in the digital finance domain. Ultimately, this study contributes to a deeper understanding of the intersection between gender dynamics and digital payment systems, offering insights to policymakers, financial institutions, and technology providers seeking to promote gender equality and financial inclusion in the digital era.